The Past, Present, and Future of Brown's Mandate: A View from North Carolina. (May 2022) - Mickelson, Roslyn A.; Ayscue, Jennifer B.; Bottia, Martha C.; Wilson, Jerry J.
The unanimous 1954 Brown v. Board of Education opinion is one of the most consequential legal decisions of the 20th century. Even though it concerned government sanctioned racial segregation of public schools, many legal scholars, policy makers, and citizens see Brown's impact going well beyond ordering the dismantling of de jure segregated public schools and instituting desegregated ones that would provide equitable high quality public education to all students irrespective of their race. Brown's mandate overturned the notorious Plessy decision sanctioning legal segregation and exposed the fiction that separate could be equal in any institution or sphere of public life. But, progress toward Brown's literal and figurative mandate has been halting and, at best, uneven. This article considers the question of whether the nation will achieve Brown' s mandate by its 100th anniversary in 2054. The authors reflect upon the relevant history of progress in Brown's implementation and the current retrenchments on those gains that have returned this nation's schools, in some districts, to pre- Brown levels of segregation. Using the state of North Carolina as a strategic case study, they speculate about the sets of social forces that may either discourage or encourage realization of Brown ' s mandate going forward. In doing so, they note population changes, national and local political factors, and other events that will either make it more or less likely that Brown's mandate will be realized by 2054.